Time-dependent or state-dependent price setting? Micro-evidence from German metal-working industries - Harald Stahl (European Central Bank (ECB), 2005)
Price setting in German metal-working industries is analysed using a monthly panel of individual price data for more than 2,000 plants covering the period from 1980 to 2001. Motivated by several models in the literature, a duration model is estimated. Price changes can be explained by a combination of state-dependence and time-dependence. Time-dependence clearly dominates and is strongest if a price increase follows a price increase. This occurs most likely after 1, 4, 5, 8, 9, … quarters. This time-dependent effect is so strong and cost and price increases are so weak in the observed period that adjustment occurs before the sticky price sufficiently deviates from the flexible price, as traditional menu cost models assume. State-dependence seems to be most relevant in periods with decreasing demand. Then firms reduce prices and the time between two price cuts only rarely exceeds four months.
Keywords: D43; E31; L11; 330; business survey data; duration analysis; E31; Classification-JEL: D43; L11; price rigidity; Metallindustrie; Preisrigidität; Preismanagement; Zeit; Deutschland